The regenerative revolution in dentistry: stem cells as the future of oral health - Jain, Muskan; Yadav, Rakesh Kumar; Verma, Promila; Bharti, Ramesh; Shakya, Vijay Kumar (International Journal of Research in Medical Sciences, 2025)
Stem cell-based therapies represent a transformative frontier in regenerative dentistry, offering biologically driven solutions for the restoration of dental and craniofacial tissues. Unlike conventional approaches that rely on synthetic materials, regenerative dentistry utilizes the self-renewing and multipotent nature of stem cells to regenerate pulp, dentin, periodontal ligaments, and even alveolar bone. Various stem cell sources- such as dental pulp stem cells (DPSCs), stem cells from human exfoliated deciduous teeth (SHED), periodontal ligament stem cells (PDLSCs), bone marrow mesenchymal stem cells (BMMSCs), and adipose-derived stem cells (ADSCs)- demonstrate diverse regenerative potentials suited for specific dental applications. Clinical advances include pulp-dentin complex regeneration, periodontal tissue repair, and jawbone reconstruction using stem cells combined with bioactive scaffolds and growth factors like BMPs, VEGF, and PDGF. Innovations in 3D bioprinting, scaffold engineering, and cell-free therapies using exosomes continue to enhance therapeutic outcomes. Despite promising results, challenges remain in standardization, immune compatibility, and cost-effectiveness, alongside ethical constraints particularly regarding embryonic stem cells. Ongoing clinical trials and emerging technologies like CRISPR gene editing and artificial intelligence offer new avenues for precision regenerative therapies. As personalized dental medicine evolves, interdisciplinary collaboration will be key to translating laboratory success into accessible, scalable clinical solutions. Stem cells not only offer hope for functional tissue regeneration but also mark a paradigm shift in patient-specific dental care.